2021
DOI: 10.1002/elan.202100392
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical Immunosensor for the Sensitive Detection of Alzheimer's Biomarker Amyloid‐β (1–42) Using the Heme‐amyloid‐β (1–42) Complex as the Signal Source

Abstract: The amyloid-β peptide (1-42) (Aβ 42 ) can provide high diagnostic accuracy for the early diagnosis of Alzheimer's disease (AD). In this study, an immunosensor based on the peroxidase-like activity of heme-Aβ 42 was designed for Aβ 42 detection. The glassy carbon electrode (GCE) was electrodeposited Au particles (GCE/Au). The GCE/Au was modified using polythionine-methylene blue (PTHÀ MB), AuNPs, monoclonal antibody (anti-Aβ 42 ), and bovine serum albumin (BSA), successively. The GCE/Au/PTHÀ MB/AuNPs/anti-Aβ 42… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 78 publications
0
1
0
Order By: Relevance
“…Alzheimer's disease is typically only identified after the commencement of the disease, so there is an urgent need to create diagnostic techniques for early disease markers. Ding et al produced an immunosensor for the detection of Aβ 42 peptides depending on the heme covalently bound to Aβ 42 possessing peroxidase-like activity [13]. Fc was chosen as signal indicator, as seen in Figure 2.…”
Section: Redox-couple-labeled Electrochemical Immunosensorsmentioning
confidence: 99%
See 2 more Smart Citations
“…Alzheimer's disease is typically only identified after the commencement of the disease, so there is an urgent need to create diagnostic techniques for early disease markers. Ding et al produced an immunosensor for the detection of Aβ 42 peptides depending on the heme covalently bound to Aβ 42 possessing peroxidase-like activity [13]. Fc was chosen as signal indicator, as seen in Figure 2.…”
Section: Redox-couple-labeled Electrochemical Immunosensorsmentioning
confidence: 99%
“…The constructed device has a detection range of 1:1000-1:200 v/v for SARS-CoV-2. [13]. Copyright (2021) John Wiley.…”
Section: Horseradish Peroxidasementioning
confidence: 99%
See 1 more Smart Citation
“…Ding et al, 2021, reported an Aβ immunosensor using a heme-Aβ (1-42) conjugated structure as a signal amplifier to detect the analyte in serum and saliva [76]. A GCE (diameter: 3 mm) was activated using CV in 0.5 M H 2 SO 4 under potential from −0.5 to 1.6 V. Then, the electrode surface was modified with AuNPs through the electrodeposition of a HAuCl 4 solution via the CV technique.…”
Section: Electrochemical Immunosensing Of Aβmentioning
confidence: 99%
“…Depending on the requirements, available equipment, and labor ability, each technique can be applied reasonably and effectively. Moreover, Aβ peptides can be detected using labels with enzymes, nanozymes, or anti-IgG-ALP, [ 86 , 87 ] or label-free using functional groups [ 88 , 89 , 90 ] in electrochemical detection methods.…”
Section: Recent Research On Aβ Detection By Electrochemical Sensorsmentioning
confidence: 99%